Plantar pressure distribution evaluation in children with down syndrome from 2 to 5 years old - Paula Silva de Carvalho Chagas; Riuraly Caroline Barreiros Fortunato Rangel; Sulamita Saile de Jesus Oliveira Dornelas; Anderson Daibert Amaral; Flávio Augusto Teixeira Ronzani; Érica Cesário Defilipo (Editora Champagnat, 2019)
Abstract Introduction: Some peculiar features of Down Syndrome (DS), such as ligament laxity, hypotonia, delay in gait acquisition, among others, may generate alterations in the distribution of plantar pressures, modifying the plantar support. Objective: To verify whether there are differences in the evaluation of plantar pressure distributions in standing posture between the measurement instruments (Baropodometer, SAPO, and Radiography). Method: This was a cross-sectional study, evaluating ten children with SD and ten children with normal development (ND), aged from two to five years old. Bio-photogrammetry, baropodometry, and foot radiography were used to assess the plantar pressure distribution. Kappa analysis was used to evaluate the agreement index between the different instruments. Results: Children with DS and ND had a higher prevalence of pronated feet in all three instruments, with poor to substantial agreement among the instruments. Conclusion: According to this study instruments, there was a greater prevalence of pronated feet in the two groups . Differences in the evaluation of the distribution of plantar pressures in the standing posture between the Baropodometer, SAPO, and radiography were observed. These instruments should be used in a complementary manner, as they propose to evaluate different aspects of the feet alignment.